Perilaku Konsumen Generasi Z dalam Penggunaan E-Wallet: Perspektif Maqashid Syariah - Chaniado Anggara, Rio; Nurwahidin; Izdiyan Muttaqin, Mohammad (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
The use of electronic wallets (e-wallets) is increasingly popular among Generation Z, known for their high-tech skills and strong propensity to adopt digital innovations in various aspects of daily life. E-wallets offer a fast, efficient, and practical means of financial transactions. However, it is important to evaluate their compliance with the principles of Maqashid Sharia, which include the protection of religion, life, intellect, descendants, and property. This study uses an interdisciplinary approach between Islamic Economics and Financial Technology (Fintech) to analyze the implementation and impact of e-wallet use among Generation Z in Indonesia. This approach allows for a more comprehensive understanding of the impact of e-wallets not only economically, but also socially and spiritually, within the framework of Islamic values. The results show that the majority of Generation Z utilizes e-wallets due to their efficiency, ease of access, and transaction security, where encryption and double verification systems are considered capable of protecting user data and maintaining the hifz al-mal (protection of property). From a hifz al-din and hifz al-'aql perspective, e-wallet use is considered legally neutral as long as it is not used for transactions that conflict with Sharia principles, such as online gambling or the purchase of illicit goods. Research also found that awareness of Sharia and digital security aspects remains relatively low, necessitating more intensive Sharia financial education and literacy for Generation Z.